Fundamental of Entrepreneurship ENT300 Lycant Services / Nurul Hazirah Mohammad Salleh... [et.al] - Mohammad Salleh, Nurul Hazirah; Bolkiah, Nur Syuhadah; Sa'adl, Saiful Ashraf; Bujang, Mohamad Azizy (2015)
Lycant Services is one of the services that provide shuttle service in Desa 11mu. The Lycant Services is in the form of partnership which consists of four members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is shuttle service. There are no sleeping partners and all partners are entitled to participate in the business management. We had agreed that Nurul Hazirah Bintl Mohammad Salleh as our General Manager and Administration Manager, Nur Syuhadah Binti Bolkiah as Marketing Manager, Saiful Ashraf Bin Sa'adl as Operating Manager, and Mohamad Azizy Bin Bujang as Financial Manager, The selection of General Manager is based on consensus among all the partners and selected based on experiences, skills and ability of the partner. The management team will be led by General Manager and assist by the other managers We are believed that we will successfully compete with our competitors in a few years ahead. This is because nowadays people use their own car to go anywhere.